Molecular basis of resistance to proteasome inhibitors in hematological malignancies - Niewerth, Denise; Jansen, Gerrit; Assaraf, Yehuda G.; Zweegman, Sonja; Kaspers, Gertjan J.L.; Cloos, Jacqueline (Drug resistance updates, 2015)
Over the past decade, the proteasome inhibitor bortezomib (Velcade) has not only gained a cornerstone position in the treatment of hematological malignancies, particularly multiple myeloma and mantle cell lymphoma, but also in experimental therapeutics of acute leukemia. However, the therapeutic efficacy of bortezomib is hampered by the emergence of acquired resistance, for which multifactorial mechanisms have been identified. This review summarizes the current status of the molecular mechanisms underlying resistance to proteasome inhibitors that emerged in preclinical therapeutic studies, and discusses these findings in the clinical perspective of novel therapeutic modalities of hematological malignancies. The specific topics that will be addressed in the current review include the recently established mechanisms of resistance to proteasome inhibitors: the role of constitutive and immunoproteasomes, mutations in proteasome subunits, unfolded protein response, XBP1 and MARCKS proteins, multidrug efflux transporters, aggresomes and autophagy, as well as the impact of pro-survival signaling pathways and bone marrow microenvironment. The growing knowledge of the determinants that confer bortezomib resistance and/or toxicity has provided the basis for the rational development of second generation proteasome inhibitors, some of which were recently approved or that are undergoing clinical evaluation as novel strategies to overcome bortezomib resistance as well as to enhance clinical therapeutic efficacy along with minimal side effects. Collectively, these combined approaches should enhance therapeutic efficacy and outcome in patients with hematological malignancies.